Implementation of a Raspberry Pi Trainer for the Subject of Microprocessors and Microcontrollers in Vocational High Schools - Enjang Akhmad Juanda; Nurul Wahidah; M. Khairudin; Z. Mohamed (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
A Raspberry Pi Trainer is a tool which is able to support and facilitate the learning process of the subject of microprocessors and microcontrollers. The objective of this study was to find out the process and the results of the implementation of a Raspberry Pi Trainer for the subject of microprocessors and microcontrollers in the expertise program of industrial electronics in vocational high schools. This study used a qualitative method. The descriptive data were resulted from the observed students’ behavior in the form of the research informants’ activities covering the domains of cognitive, psychomotor, and affective. There were 20 informants divided into two classes, 10 in class XII A and 10 in class XII B. Each class consisted of 2 males and 8 females. The results showed the Raspberry Pi Trainer was well applied in practical learning activities. The average abilities of class XII B and class XII A for the domains of cognitive, psychomotor and affective were categorized as very good, good and moderate respectively.